Tuberculosis preventive treatment in newborns - Tony TannousTahan; Andrea Maciel de Oliveira Rossoni; Giuliana Lugarini; Simoni Pimenta de Oliveira; Juliana Taques; Mauricio Bedim dos Santos; Betina Mendez Alcântara Gabardo; Tatiane Emi Hirose; Cristina de Oliveira Rodrigues (Jornal de Pediatria)
Objective: To describe the reported cases of newborns subjected to tuberculosis preventive treatment (TPT) in the state of Paraná, Brazil, and to evaluate the safety and effectiveness in preventing the progression of TB disease in this population. Method: Observational, descriptive case series, with secondary data. The characteristics of the participants were analyzed from the information systems of preventive treatment of TB (of Paraná), between 2009 and 2016. To evaluate which children had developed tuberculosis later or died, we used the data from the information systems of TB (in Brazil), and mortality (in Paraná), covering the years 2009 to 2018. Results: A total of 24 children underwent TPT with the age at treatment onset ranging from 0 to 87 days (median: 23 days). In 95.8 %, the exposure occurred at home, and in 33.3 % of cases, the mother was the source of the infection. A total of 20.8 % of the children tested positive for tuberculosis test at 3 months of age, 83.3 % completed treatment, and 2 experienced adverse events (gastrointestinal issues). No children developed TB or died during the minimum of a 2-year evaluation period through the official databases. Conclusions: In this case series, the adherence to the plan was high, with few adverse events and 100 % protection against infection.